A Study on Thermal Insulation of Cement Bricks Incorporate with Cellulose Fiber - Kamaruzzaman, Ahmad Syamir; Wan Jusoh, Ts. Dr. Wan Amizah (Progress in Engineering Application and Technology, 2023)
Cement brick is one of the important and common building materials thatwidely being used in the construction industry. Common brick that being using in theconstruction industry nowadays are poor in thermal insulation. The objective of thisstudy is to study the physical properties of cellulose fiber as added material in cementbricks. Next, this study is to determine the mechanical properties of cement brickscontaining cellulose fiber. Lastly to evaluate the thermal performance for cementbrick containing cellulose fiber compare with conventional cement bricks. Thematerials that being used is the cellulose fiber powder made from the bamboo plantwith different percentage that added into the mixture of cement bricks. The test thathas being carried out for this study is the density test, water absorption test, ultrasonicpulse velocity test, compressive strength test and thermal conductivity test. From thisstudy, it can be observed that the value of the thermal conductivity of the bricks forthe specimens sample of 10% obtained the lower value of thermal conductivity with0.153 W/mᵒC for the age of 7 days of curing and 0.161 W/mᵒC for the age of 28 daysof curing and the density is 2335.71 kg/m3for 7 days and 2345.24 kg/m3for 28 dayswith the compressive strength of 33.18 kN/m2and 41.04 kN/m2 for 7 days and 28days. From the result that has obtained, the value of thermal conductivity of allspecimens has meet the standard requirements for thermal conductivity which is 0.69W/mᵒC and below. The good production of bricks should obtain low thermalconductivity so that the buildings that use the bricks is cool in summer especially inthe hot weather in Malaysia.